A qualitative analysis of factors impacting resilience among youth in post-conflict Liberia. Issue 1 (December 2016) - Levey, Elizabeth; Oppenheim, Claire; Lange, Brittany; Plasky, Naomi; Harris, Benjamin; Lekpeh, G. Gondah; Kekulah, Isaac; Henderson, David; Borba, Christina
Abstract Background In 2008, 5 years after the Liberian civil war ended, there were an estimated 340, 000 orphans in Liberia, 18 % of the total child population of the country. Given that children make up half the population and that these children experienced significant trauma and loss both through direct exposure to the war and then to the Ebola epidemic, and indirectly as a result of the trauma experienced by their parents, the recovery of these children is essential to the recovery of the nation as a whole. The goal of this research was to identify factors contributing to resilience among youth in post-conflict Liberia. Resilience was defined as evidence of adaptive functioning and psychological health. Methods Seventy-five young people (age 13–18) in the capital city of Monrovia, Liberia were recruited in 2012. Semi-structured interviews were conducted, and demographic data were collected. Interviews were then transcribed and coded thematically. Results Forty-six of the participants were attending school, and 29 were not enrolled in school. Youth enrolled in school demonstrated greater adaptive functioning. This was particularly true for boys in any school setting and girls attending private school. Youth not attending school were more likely to have lost family members or become estranged from them, and many were also engaging in substance use. Emotion regulation, cognitive flexibility, agency, social intelligence and, in some cases, meaning-making were found in participants who showed resilient outcomes. Conclusions Caregiver relationships mediate the development of psychological capacities that impact resilience. These findings suggest that youth who have lost a caregiver, many of whom are not attending school, are experiencing a significant ongoing burden in terms of their daily functioning and psychological health in the post-war period and should be the focus of further study and intervention targeting substance use and community reintegration. Trial registration Partners Healthcare IRB Protocol# 2012P000367.